Modeling and management vibroacoustic emission homogeneous plate under the action of external forces concentrated - Макаренко В.M. (Proceedings of National Aviation University (archive), 2009)
The model of rectangular plate acoustic radiation and transverse motion were presented, and its investigation was performed. The solution is received based on classisal plate theory. Vibration response and sound radiation of plates with simply-supported boundary conditions was discussed. Concentrated harmonic forces are used as an external excitation. The general confirmities to the law have been established for the changes of sound radiation, depending on the parameters of external excitations. An experiment was performed for justification of analytical approach, which is used for computations. Eigenfrequencies of free plate oscillations, which are received analytically, are in good agreement with experimental results.